Powersharing White House cabinet relations in the modern presidency - Warshaw, Shirley Anne 1950- (State Univ. of New York Press, 1996)
The complex relationship between the White House staff and the presidential cabinet has changed dramatically in the last twenty-five years. During that time, the White House has emerged as the center of power in the domestic policy process, leaving the departments with a diminishing role in initiating major policy proposals. This book focuses on powersharing between the White House has become the dominant player, relegating the departments to implementation, rather than design, of key initiatives. Powersharing begins with an overview of the role of the modern cabinet and a discussion of the cabinet's emergence in a policy role, and then in a chapter-by-chapter analysis of presidential administrations from Nixon through Clinton chronicles the shifting balance of power from the departments to the White House in both the design and management of the nation's major domestic programs. The book concludes with an assessment of the prospects for effective powersharing between the cabinet and the White House staff.
Keywords: USA -- Government; USA -- Präsident; Geschichte 1969-1995; Kabinetten (politiek); Machtsverhoudingen; Presidentschap; Politik; Cabinet officers -- United States; Executive departments -- United States; Presidents -- United States; Presidents -- United States -- Staff; USA; United States -- Politics and government -- 1945-1989; United States -- Politics and government -- 1989-